Coups and economic crises - Christian Bjørnskov (Research Institute of Industrial Economics (IFN), 2022)
This paper explores whether coups cause increased crisis risk, and if some types of coups are associated with stronger risk. I use a worldwide sample with data on more than 1200 onsets of economic crisis between 1950 and 2019, treat separate effects of military and civilian coup attempts, and distinguish between failed and successful coups. The data reveal that economic crises are primarily induced by successful coups, and by coups that result in regime change towards civilian autocracy from both democracy and military dictatorship.
Keywords: O11; O43; P16; 330; Democracy; Autocracy; Regime Types; Crisis